Electrochemical properties of PVA-GO/PEDOT nanofibers prepared using electrospinning and electropolymerization techniques - Zubair, Nur Afifah; Abdul Rahman, Norizah; Lim, Hong Ngee; Mohd Zawawi, Ruzniza; Sulaiman, Yusran (Royal Society of Chemistry, 2016)
Conducting nanofibers composed of poly(vinyl alcohol) (PVA), graphene oxide (GO) and poly(3,4-ethylenedioxythiophene) (PEDOT) were fabricated via a combined method using electrospinning and electropolymerization techniques. A small amount of GO was dispersed into PVA as the precursor solution for electrospinning, resulting in free-bead nanofiber structures with a diameter range less than 200 nm. SEM images of the obtained nanofiber revealed that PEDOT grew well on the surface of the electrospun nanofibers during the potentiostatic mode of the electropolymerization process. The presence of GO and PEDOT was confirmed by FTIR and Raman spectroscopy analyses. Comparing with the PVA/PEDOT nanofiber, the experimental results indicate that the addition of GO improved the electrochemical performance of the nanofibers. The electrochemical measurements demonstrated that the PVA–GO/PEDOT composite nanofiber could enhance the current response and reduce the charge transfer resistance of the nanofiber.